PENGARUH PEMBERIAN PAKAN KULIT SAPI TERHADAP PERTUMBUHAN dan KELANGSUNGAN HIDUP BENIH LOBSTER PASIR (Panulirus homarus) - sherina aulia ningtias tias; Muhammad Junaidi; Ibadur Rahman (Jurnal Perikanan Unram, 2019)
This study aims to determine the effect of giving cow skin on growth and survival of lobster sand (Panulirus homarus). The method used in the study was an experimental method using a randomized block design (RCBD), with 5 treatments namely giving 100% trash fish, 75% trash fish + 25% cow skin, 50% trash fish + 50% cow skin, 25% fish trash + 75% cow leather and 100% cow leather repeated 3 times. observations carried out for 60 days. The parameters observed include absolute growth, specific growth rate, feed conversion ratio and survival rate. The results showed that absolute growth and the highest specific growth rate were found in rooting 3 (50% trash fish + 50% cow skin), which had a significantly different effect (P<0.05). Based on this study, to use feed with 50% trash fish + 50% cow leather and perform proximate tests on raw and boiled cow skin.